Embodiment in Old Age - Marcin Muszyński (Jesuit University Ignatianum in Krakow, 2023)
RESEARCH OBJECTIVE: This article presents embodiment in relation to four areas of human agency. The findings are part of a larger project on learning to be old. THE PROBLEM AND RESEARCH METHODS: The main research problem is understanding how strategies, actions, and attitudes toward one's body differ among the study participants in various agency areas. The study is based on a constructivist paradigm and grounded theory methodology. THE PROCESS OF ARGUMENTATION: Four fields of the agency have been presented on a continuum, where on one side, forces are pushing a person towards dependence, while on the other side, there is the individual's independence. These areas were identified during the analysis of empirical data and allow for a departure from judgmental approaches to aging, serving as model areas for the functioning of an older adult . These areas were used to reflect on the embodiment of older people. Finally, the embodiment category was placed within broader structures such as discourses, concepts, and theoretical knowledge about aging and getting old. RESEARCH RESULTS: The findings indicate the multidimensional nature of the aging body. Different strategies, actions, and attitudes towards one's embodiment are activated depending on the individual's life situation and social position. CONCLUSIONS, INNOVATIONS, AND RECOMMENDATIONS: Embodiment occupies a special place in learning to be old. It is one of the primary regulators of this process. As it turns out, self-identification is primarily related to the body. Furthermore, the findings of this study allow moving away from a narrow understanding of aging as physical deterioration and decay.